Studies of ionizing radiation shielding effectiveness of silica-based commercial glasses used in Bangladeshi dwellings - Yasmin, Sabina; Barua, Bijoy Sonker; Khandaker, Mayeen Uddin; Chowdhury, Faruque-Uz-Zaman; Rashid, Md. Abdur; Bradley, David Andrew; Olatunji, Michael Adekunle; Kamal, Masud (Elsevier, 2018)
Following the rapid growing economy, the Bangladeshi dwellers are replacing their traditional (mud-, bamboo-, and wood-based) houses to modern multistoried buildings, where different types of glasses are being used as decorative as well as structural materials due to their various advantageous properties. In this study, we inquire the protective and dosimetric capability of commercial glasses for ionizing radiation. Four branded glass samples (PHP-Bangladesh, Osmania-Bangladesh, Nasir-Bangladesh, and Rider-China) of same thickness and color but different elemental weight fractions were analyzed for shielding and dosimetric properties. The chemical composition of the studied material was evaluated by EDX technique. A well-shielded HPGe γ-ray spectrometer combined with associated electronics was used to evaluate the attenuation coefficients of the studied materials for 59 keV, 661 keV, 1173 keV and 1332 keV photon energies. A number of shielding parameters- half value layer (HVL), radiation protection efficiency (RPE) and effective atomic number (Zeff) were also evaluated. The data were compared with the available literature (where applicable) to understand its shielding capability relative to the standard materials such as lead. Among the studied brands, Rider (China) shows relatively better indices to be used as ionizing radiation shielding material. The obtained, Zeff of the studied glass samples showed comparable values to the TLD-200 dosimeter, thus considered suitable for environmental radiation monitoring purposes.